PENGARUH VARIASI FLY ASH SEBAGAI PENGGANTI SEBAGIAN SEMEN DENGAN COPPER SLAG PENGGANTI SEBAGIAN PASIR UNTUK BETON MUTU 42 MPA - Ferdian Adhitia; Dewi Pertiwi (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2020)
At the smelting plant of PT Smelting Company Gresik produces waste in the form of copper slag. Copper slag waste has several advantages including increasing concrete compressive strength, reducing heat hydration, increasing resistance to sulfate in seawater, reducing alkali-silica and chloride attack. Probolinggo power plant there is the waste product from burning coal. The waste is divided into two types. The flying waste is fly ash obtained by being captured by other particle filtration equipment before the exhaust gas reaches the coal chimney. Whereas the waste that goes down is called bottom ash. This study uses copper slag waste as a partial replacement for sand with fly ash as a partial replacement for cement. The variant used are 40% copper slag, 40% copper slag + 5% fly ash, 40% copper slag + 7.5% fly ash, 40% copper slag + 10% fly ash. Copper slag comes from PT. Smaleting Company Gresik, while the fly ash from PT. Paiton. Tests carried out at PT. SCG Readymix. Test carried out at the age of 14 days, 28 days and 56 days. Normal concrete compressive strength was obtained more than 42 MPa, the highest compressive strength at a variation of 40% copper slag + 10% fly ash with compressive strength of 58.13 MPa at the age of 56 days.